The Accountability of Football as a Form of Public Good on Local Communities: A Pilot Study - Raiola, Gaetano; D’Elia, Francesca; Esposito, Giovanni; Altavilla, Gaetano; D’Isanto, Tiziana (Physical Education Theory and Methodology, 2023)
Research purpose. Football is a social phenomenon, especially due to the enormous use of the media and the economic and financial implications that derive from its complex sporting activities. Amateur sports associ-ations (ASD) are part of this phenomenon since they represent socio-educational agencies that pursue the aims of sports training by adopting specific educational, social, and economic models. Individually, they have modest dimensions but considered in an aggregate manner, they present a significant and not negligible dimension in society. The purpose of the study is to try to understand the stakeholders’ perceptions concerning the issues of youth football and the accountability that football, understood as a public good, produces in local communities. Materials and methods. The study was conducted through a survey submitted to a sample made up by presidents and trainers of 112 amateur sports clubs in the province of Salerno, a city in Southern Italy. The survey includes two thematic sections. The first section presents 6 items, common for both presidents and trainers, about the various social and educational issues related to the practice of the sport. The second section presents 4 items, that analyse the contribution that the U.S. Salernitana 1919 football club, considered as a “public good”, brings to the territory in terms of economic and social return. Validity and reliability were calculated. The collected data were analysed using the Chi-square (χ2) test to check the correlation between the responses given by the stakeholders. Results.The results show a concordance of opinions among the stakeholder regarding the most relevant educational aspects related to the practice of football, and the major critical issues involving the youth academy of U.S. Salernitana 1919 football club. Conclusions. These results highlight the stakeholders’ full awareness of the potential positive social effects of the presence of football ASDs in the territory, even considering the limitations of the study sample and the territorially circumscribed objective of the research.